Preparation of acrylic silicon dioxide nanoparticles as a binder for leather finishing. Issue 8 (5th July 2018) - Mohamed, Ola; Elsayed, Hamed; Attia, Rasha; Haroun, Ahmed; El‐Sayed, Nabil
Abstract: Polyacrylic resin, methyl methacrylate and 2‐ethyl hexylacrylate, was prepared via microemulsion polymerization with ratio 2:1, and then modified with silicon dioxide nanoparticles (SiO2 ) prepared by sol–gel process. Different ratios of these nanoparticles combined with acrylic resins were then coated on leather surface. The physical, chemical, and mechanical properties of coated leather were evaluated through various instrumental analysis as nuclear magnetic resonance, Fourier transmission infrared, dynamic light scattering, thermal gravimetric analysis, energy‐dispersive X‐ray spectroscopy, and transmission electron microscope. Water vapor permeability was improved with increase in the percentage of the nanoparticles. Tensile, tear strength, and elongation percentage were increased up to 3% of SiO2 nanoparticles followed by decreasing behavior. The acrylate water‐based SiO2 nanoparticles exhibited good eco‐friendly leather finishing system. Abstract :